2017
DOI: 10.1186/s12879-016-2108-8
|View full text |Cite
|
Sign up to set email alerts
|

Better care provided to patients with tuberculosis at county designated TB hospitals (CTD) compared to non-CTDs in rural China

Abstract: BackgroundThe primary unit of tuberculosis (TB) medical care in China is the county TB dispensary or county designated hospital (CTD), where patients can receive free diagnosis and treatment. However, a substantial number of patients seek their anti-TB treatment from general health facilities (Non-CTDs). This study aimed to investigate the first anti-TB treatment experience and choice of health facilities of retreated TB patients and their determinants.MethodsA cross-sectional study was conducted in Jiangsu, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Of course, this relationship should not all impute to the rural patients, but to the health-care resources they live in. 37 , 39 Previous studies have shown that the medical staff in rural medical institutions received less medical education and limited knowledge in medical service delivery, 38 so doctors were not able to provide satisfactory health education and counseling services to patients, 40 which could lead to patients’ low communication willingness, non-ideal enthusiasm and less initiative to participate in anti-TB treatment. 19 , 41 Further SEM results revealed that the treatment adherence of rural patients played a mediating role in the doctor–patient communication predicting the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, this relationship should not all impute to the rural patients, but to the health-care resources they live in. 37 , 39 Previous studies have shown that the medical staff in rural medical institutions received less medical education and limited knowledge in medical service delivery, 38 so doctors were not able to provide satisfactory health education and counseling services to patients, 40 which could lead to patients’ low communication willingness, non-ideal enthusiasm and less initiative to participate in anti-TB treatment. 19 , 41 Further SEM results revealed that the treatment adherence of rural patients played a mediating role in the doctor–patient communication predicting the treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was evident that HCV RNA could be detected in almost all DBS samples. LOD for HCV RNA from DBS samples is entirely dependent on the used NAT assay and has been estimated between 58 IU/mL to more than 250 IU/mL [ 12 , 87 ]. Absolute quantification of HCV RNA should not be considered and seems impractical while using DBS specimens for HCV RNA quantitative analysis.…”
Section: The Existing and Current Paradigms Of Hcv Diagnosticsmentioning
confidence: 99%
“…One study predicts the consolidated specificity and sensitivity of 98% for HCV RNA detection for both DBS specimen and venipuncture blood samples [ 12 ]. In a meta-analysis, based on an evaluation of the diagnostic accuracy of laboratory-based screening for HCV in dried DBS samples, the pooled diagnostic accuracy for HCV RNA detection was found as: specificity 99.2%, sensitivity 97.8%, PPV 44.8, NPV 0.04, with a diagnostic odds ratio (DOR) 1966.9 [ 87 ]. In another study, Aptima HCV Quant Dx assay (Hologic Inc, Danbury, CT) was evaluated for HCV RNA detection from DBS and venipuncture collected specimen.…”
Section: The Existing and Current Paradigms Of Hcv Diagnosticsmentioning
confidence: 99%
“…The total reported funding gap is $1.6 billion, with the largest gaps observed in Indonesia ($340 million), Nigeria ($256 million), the Philippines ($164 million), and China ($109 million) [1]. Although the Chinese government has provided free services for basic TB examinations and treatment, as well as the fact that health insurance policies also cover essential services/ medicines within a defined insurance benefits package, TB patients still experience a considerable financial burden [2,3]. According to the 2022 WHO data, among the top four countries with the largest funding gaps mentioned above, the largest average expenditure per TB patient is in China ($848.078), followed by Nigeria ($693.941), Indonesia ($241.342), and the Philippines ($190.077).…”
Section: Introductionmentioning
confidence: 99%